Building energy index: A case study of three government office buildings in Malaysia - Tahir, Mohamad Zamhari; Mohd Nawi, Mohd Nasrun; Rajemi, Mohamad Farizal (American Scientific Publishers, 2015)
This paper presents the findings of a study to investigate energy consumption for three selected government office buildings in Malaysia and to determine the Building Energy Index (BEI) for each building.The main purpose of this study is to review how much the buildings utilized energy and then to identify factors affecting energy usage. To obtain basic information and data, the analysis was performed based on the data gathered, on-site survey and qualitative assessment on the building and its systems.Building Energy Index (BEI) is used for comparing energy consumption in buildings for one year and measured in kilowatts hours divided by the gross floor area of the building in square meters.Based on BEI MS 1525:2007 Standard of 136 kWh/m2/year, there is only one of selected building has achieved BEI below than requirement standard for energy efficient building in Malaysia.In the end, factors that affecting inefficient energy consumption will provide researcher to propose appropriate energy saving approaches in future study.At the meanwhile for a long term solutions and consistent energy savings, it can be achieve by implementing energy efficient design with sustainable technologies in the early stage of construction to maintain the best environment of workplace while minimizing the energy cost.